Development of DPP-4-resistant CXCL9-Fc and CXCL10-Fc chemokines for effective cancer immunotherapy - Jennie Lugassy; Noor Abdala-Saleh; Ghada Jarrous; Abeer Turky; Daniel Saidemberg; Gabriela Ridner-Bahar; Nir Berger; Dana Bar-On; Tetsuya Taura; David Wilson; Nathan Karin (Proceedings of the National Academy of Sciences, 2025)
CXCR3 is a chemokine receptor for three ligands: CXCL9, CXCL10, and CXCL11. Accumulating evidence, including data presented here, suggests that the interaction between CXCL9/CXCL10 and CXCR3 not only attracts CXCR3+ T cells but also promotes the induction of IFNγ- high effector/cytotoxic CD4+ and CD8+ T cells, establishing a CXCL9/10-CXCR3-IFNγ self-amplifying cycle that promotes efficient cancer cell killing. One of the homeostatic mechanisms that may limit this cycle is the cleavage of the two N-terminal amino acids of these chemokines by Dipeptidyl Peptidase IV (DPP-4). The modified chemokines retain their ability to bind CXCR3 but no longer activate it, becoming competitive antagonists to native CXCL9/CXCL10. To develop a DPP-4-resistant variant, we combined biochemical analysis with computational modeling, demonstrating that the addition of N-terminal glutamine (Q) to CXCL9-Fc and CXCL10-Fc rendered them fully active CXCR3 agonists, yet resistant to DPP-4 cleavage. Preclinical evaluations imply that they offer significant therapeutic potential in cancer immunotherapy.